2012
DOI: 10.1038/cgt.2012.56
|View full text |Cite
|
Sign up to set email alerts
|

Sindbis viral vectors target hematopoietic malignant cells

Abstract: Sindbis viral vectors target and inhibit the growth of various solid tumors in mouse models. However, their efficacy against blood cancer has not been well established. Here, we show that Sindbis vectors infect and efficiently trigger apoptosis in mouse BW5147 malignant hematopoietic T-cells, but only at low levels in human lymphoma and leukemia cells (Jurkat, Karpas, CEM, DHL and JB). The Mr 37/67 kD laminin receptor (LAMR) has been suggested to be the receptor for Sindbis virus. However, JB cells, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Moreover, the mechanisms of protein synthesis directed by SINV mRNAs are helping to shed light on the structure-function relationship of viral mRNAs. From a practical viewpoint, SINV has been employed in fields as diverse as cancer therapy and has aided in the understanding of the adaptive antiviral response [ 8 , 9 ]. In the current review, we will summarize what is known about the mechanisms of translation of SINV mRNAs, with a focus on the initiation events of non-canonical translation of subgenomic mRNA (sgRNA).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the mechanisms of protein synthesis directed by SINV mRNAs are helping to shed light on the structure-function relationship of viral mRNAs. From a practical viewpoint, SINV has been employed in fields as diverse as cancer therapy and has aided in the understanding of the adaptive antiviral response [ 8 , 9 ]. In the current review, we will summarize what is known about the mechanisms of translation of SINV mRNAs, with a focus on the initiation events of non-canonical translation of subgenomic mRNA (sgRNA).…”
Section: Introductionmentioning
confidence: 99%
“…However, no tumor targeting of luciferase expression was observed, suggesting that the natural targeting observed for SIN was not a common feature for alphaviruses [62]. Moreover, related to the SIN tropism, in contrast to earlier findings suggesting laminin receptors as targets for SIN, it was discovered that although JB leukemia cells express high levels of laminin receptors, they showed low susceptibility to SIN [63]. In another study, tumor tropism was investigated in a human ML-14a xenograft model, which indicated that SIN infections are not defined by the level of SIN receptors, but by interferon (IFN) response in tumors [64].…”
Section: Oncolytic Alphavirus Approachesmentioning
confidence: 99%
“…In addition to targeting solid tumors, SIN vectors were demonstrated to efficiently trigger apoptosis in murine BW5147 malignant hematopoietic T-cells [63]. In contrast, only modest efficacy was seen in human lymphoma and leukemia cells.…”
Section: Oncolytic Alphavirus Approachesmentioning
confidence: 99%
“…Parvovirus B19[92] and sindbis[93] viruses have also been reported to exhibit oncolytic effects in hematologic malignancies, and further analyses for their clinical potential is needed.…”
Section: B Oncolytic Viruses and Applications In Hematological Maligmentioning
confidence: 99%